Using stable isotopes to estimate migratory connectivity for a patchily distributed, wetland-associated Neotropical migrant. (23rd November 2019) - Reese, Jessie; Viverette, Catherine; Tonra, Christopher M; Bayly, Nicholas J; Boves, Than J; Johnson, Erik; Johnson, Matthew; Marra, Peter; Ames, Elizabeth M; Caguazango, Angela; DeSaix, Matthew; Matthews, Alix; et al.
Abstract: Estimates of migratory connectivity are needed for full annual cycle population models of migratory bird species experiencing rapid declines in abundance. One technique to determine migratory connectivity is through stable isotope analysis. This low-resolution method may be influenced by how data are calibrated between isotopes measured in precipitation and those measured in feathers, and can be informed by incorporating relative abundance into the assignment model. eBird abundance maps are a new tool combining citizen science data into a predictive species distribution model. In the Prothonotary Warbler ( Protonotaria citrea ), a wetland-associated songbird with a patchy breeding distribution, we sought to use stable-hydrogen isotope analysis informed by a species-specific calibration equation and eBird abundance data to determine the strength of migratory connectivity. We developed a species-specific calibration equation using known-origin samples from the breeding grounds and found that stable-hydrogen isotope values measured in precipitation explained 50% of the variation in stable-hydrogen isotope values among feathers. We found that the assignment model incorporating eBird abundance data correctly identified the true origins of 66% of individuals, and that the average assignment area (as a measure of precision) was 64% of the breeding distribution. These results represented a 7% increase in precision and a 3% decrease in accuracy when compared to a model that was not informed by abundance. Based on these models, wintering populations from 6 countries represented a mix of likely breeding origins, suggesting low migratory connectivity for Prothonotary Warblers. We found evidence that wintering latitude was related to likely breeding origin, with individuals at western wintering locations more likely to have southern breeding origins, but this relationship was weak. These results corroborate studies using archival light-level geolocators and high-resolution genetic markers, which also demonstrated weak migratory connectivity in this species. For patchily distributed species, eBird abundance data may not provide a useful increase in precision and accuracy for isotope assignments.